If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying x + -5 + 14 = 48 Reorder the terms: -5 + 14 + x = 48 Combine like terms: -5 + 14 = 9 9 + x = 48 Solving 9 + x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + x = 48 + -9 Combine like terms: 9 + -9 = 0 0 + x = 48 + -9 x = 48 + -9 Combine like terms: 48 + -9 = 39 x = 39 Simplifying x = 39

| 4x+1=2x-2 | | 3k^2=0 | | 7x-10x=-20-4 | | 3x-4-x+7= | | 8x-xy=7+9x | | x^2-12x^2y+9y^2=0 | | x^2+y^2-2xy=0 | | 9x^2+y^2-6xy=0 | | 3c^3-10c^2+9c-2=0 | | 2(5-3x)=4(x+2)-4(4-5x)+7 | | 80=10+2x | | 100=0.02(X) | | 4X+29=11X-55 | | r+r+1+r+2=99 | | (3x-9)(2x-8)=0 | | (3x-9)x(2x-8)=0 | | 9X+9=5X+33 | | 99.96=0.02(X)+X | | 2p+7=1 | | 2y+2=3y+3 | | Y=x^2-2-2 | | 1.2x-2.5=0.4x+3.34 | | 2(x+4)-(2x+8)=0 | | 7y+3=12y-2 | | 0.5(3a-1)=a-5 | | 3(y+4)=5y+30 | | (4x-12)(5-2x)=0 | | 9e-2e-3+5e= | | (3x+6)(9+2x)=0 | | 5m+4=7(m+1) | | (5-2x)(6+3x)=0 | | 6(x+7)=2(x+7) | | x-4=3x | | x-4=3y | | (x+2)(x-2)=0 | | x=4+3y | | -(3y+1)-(-2y-8)=-1 | | (5x-3)(3x-3)=0 | | 5X+30=14X-60 | | 3(t-6)+5t=4(2t+5)-10 | | 5=8k-4k | | 7+7X=43+X | | x=16x-9 | | 10=x+(1.5x) | | Y=3x-24x-7 | | 8n+6=70 | | 5x+40=12x-44 | | 7.75=2(3.14)r | | 6x(7+4)= | | (3x-2)(4x+7)=0 | | N+20=28 | | y=x^2-1-1 | | y=x^2+0-1 | | y=x^2-0-1 | | 6x+7=103-6x | | -5-6=7-8x | | -8y+8=27 | | 136-4x=4x+16 | | 2405.66=0.02(X)+X | | (3x-2)-(4x+7)=0 | | 6x+5=-91-10x | | -63-8x=8x+17 | | -8-5x=6-7x | | 7-7x=59-35x | | 63717.16=0.02(X)+X |